COMPARISON OF VASOPRESSIN AND PHENYLEPHRINE IN TREATMENT OF DOPAMINE RESISTANT SEPTIC SHOCK – A RANDOMISED CONTROL TRIAL - PATRO, MADHUSMITA; MODA, NUPUR; DAS, SUSHREE; BISWAL, PRERNA (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objectives: Septic shock is associated with refractory hypotension and organ dysfunction and remains an important cause of mortality in intensive care units (ICUs). Vasopressors are the first-line treatment. The present study aims to compare vasopressin and phenylephrine in the management of dopamine-resistant septic shock in the ICU setting. Methods: The study is a prospective, open-labeled, and randomized study comparing the effects of vasopressin (Group I) and phenylephrine (Group II) in the management of dopamine resistant septic shock in intensive care set up. The parameters recorded from 0 to 6 h after persistent hypotension despite maximum dose of dopamine were: Heart rate (HR) (beats/min), systemic blood pressure (mmHg), cardiac output (L/min), cardiac index (CI) (L/min/m2), stroke volume (ml), systemic vascular resistance index (dynes/cm5/m2), oxygen delivery index (IDO) (ml O2/min/m2), urine output (ml), and serum lactate (mg/dl). Results: There was a significant difference in HR, systolic blood pressure, cardiac output, and CI in both groups from 1 h to 6 h. The IDO had a significant rise in Group II. The serum lactate level also decreased in Group II at 6 h. Conclusion: From our study, we concluded that as organ perfusion and oxygenation are more important for the treatment of septic shock and to keep the vital organs functioning rather than to increase the systemic vascular resistance and blood pressure, phenylephrine showed a better result than vasopressin in the treatment of septic shock.